Virtual and augmented reality in teaching natural sciences in primary school - Mukhina, Tetiana; Polishchuk, Kateryna (Kharkiv : H. S. Skovoroda Kharkiv National Pedagogical University, 2025)
This article explores the transformation of digital education within the framework of the New Ukrainian School (NUS), focusing on the dual pillars of teacher competence and innovative classroom technologies. The author argues that digital competence has evolved from basic ICT skills into a meta-professional quality, aligned with the European DigComp framework, which is essential for creating flexible, student-centered learning environments. A significant portion of the study is dedicated to the practical application of immersive technologies, such as Virtual Reality (VR) and Augmented Reality (AR), in teaching natural sciences to primary school students. Tools like MozaBook, Star Walk, and Google Expeditions are highlighted for their ability to foster investigative thinking and provide inclusive access for students with special educational needs. Despite the acceleration of "forced digitalization" due to pandemic and war conditions, the article concludes that sustainable progress requires a shift toward deep pedagogical design thinking and the integration of cutting-edge tools like Artificial Intelligence (AI) to optimize the educational process.
Keywords: Digital competence; New Ukrainian School (NUS); Virtual Reality (VR); DigComp framework; immersive learning; primary education; teacher professional development; inclusive education; pedagogical design thinking; artificial intelligence in education